TABOO WORDS IN JAVANESE SPOKEN IN PANEKAN VILLAGE, MAGETAN, EAST JAVA - Nafiis, Nahla Annisa Ainun; Budasi, I Gede; Dewi, Kadek Sintya (Universitas Muhammadiyah Makassar, 2024)
This research aims to identify taboo words, taboo forms, and their taboo references This study was designed in the form of a descriptive qualitative research which involved two types of data: primary and secondary. The researchers acted as the main instuments in this study. The other instrument interview guide, smartphone, and notebook. The source of data were the 3 informants selected based on a set of criteria. The identified data were analyzed as follows: the data of taboo words were analyzed into 3 domains in the concept of Tri Hita Karana. The data related to taboo form were analyzed using Frazer’s (1955) and Montagu’s theory (1973), and the data related to their referances of taboo words were analyzed using Frazer’s (1955) theory.The results of this study show that there were 44 taboo words were found and connected to the three domains of Tri Hita Karana concept. 3 related Parahyangan, 37 related to Pawongan, and 5 related to Palemahan. The 40 among 44 taboo words were classified into swearing words. 4 among the 44 taboo words identified were classified into taboo names . From the 44 taboo words were found 11 types of refrences: parent’s names (3), animal’s name (4), mentioning genital (5), sexual activity (4), wisdom of ruler (1), bodily function (6), nature (1), illness (9), name of spirit (1), personal pronouns (5), and spesific activity (5), were found..